2002
DOI: 10.1038/nsb864
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of a proline-driven conformational switch within the Itk SH2 domain

Abstract: Interleukin-2 tyrosine kinase (Itk) is a T cell-specific kinase required for a proper immune response following T cell receptor engagement. In addition to the kinase domain, Itk is composed of several noncatalytic regulatory domains, including a Src homology 2 (SH2) domain that contains a conformationally heterogeneous Pro residue. Cis-trans isomerization of a single prolyl imide bond within the SH2 domain mediates conformer-specific ligand recognition that may have functional implications in T cell signaling.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
126
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 117 publications
(131 citation statements)
references
References 32 publications
4
126
1
Order By: Relevance
“…mational change of Pro 28 . The isomerization of the prolyl imide bond has been recently attributed to the modulation of ligand recognition of proteins by controlling the relative orientation of protein-binding surfaces (86). However, the failure to observe any TOCSY connectivities among these signals makes it impossible to confirm the assignments proposed here.…”
Section: Resonance Assignmentcontrasting
confidence: 45%
“…mational change of Pro 28 . The isomerization of the prolyl imide bond has been recently attributed to the modulation of ligand recognition of proteins by controlling the relative orientation of protein-binding surfaces (86). However, the failure to observe any TOCSY connectivities among these signals makes it impossible to confirm the assignments proposed here.…”
Section: Resonance Assignmentcontrasting
confidence: 45%
“…Although all of the proline residues in the ZPR1 crystal structure adopt the trans configuration, cis isomers might occur in vivo. Indeed, it has been proposed (23) that the highly conserved proline following the invariant aspartic acid might undergo a native state cis-trans isomerization switch analogous to the proline isomerization switch that modulates ligand recognition in the SH2 domain of the IL-2 tyrosine kinase (24). The proline residue in ZPR1 is located at the N terminus of the ␤6/␤7-loop, the conformation of which would necessarily be altered by cis-trans isomerization.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that the Asn 286-Pro 287 imide bond in the Itk SH2 domain adopts both the cis and trans conformations in solution. 2,3 Exchange between the conformers is slow on the NMR time scale, leading to the appearance of doubled resonances in NMR spectra for 35 of the 109 SH2 residues (Figure 1b). The structural changes induced by isomerization of the peptidyl prolyl imide bond in the Itk SH2 domain modulate its affinity for both of its ligands.…”
mentioning
confidence: 99%